A National Catalogue of Viruses Associated with Indigenous Species Reveals High-Throughput Sequencing as a Driver of Indigenous Virus Discovery - Merlyn Robson; Kar Mun Chooi; Arnaud Gérard Blouin; Sarah Knight; Robin Marion MacDiarmid (Viruses, 2022)
Viruses are important constituents of ecosystems, with the capacity to alter host phenotype and performance. However, virus discovery cued by disease symptoms overlooks latent or beneficial viruses, which are best detected using targeted virus detection or discovered by non-targeted methods, e.g., high-throughput sequencing (HTS). To date, in 64 publications, 701 viruses have been described associated with indigenous species of Aotearoa New Zealand. Viruses were identified in indigenous birds (189 viruses), bats (13 viruses), starfish (4 viruses), insects (280 viruses), and plants (126 viruses). HTS gave rise to a 21.9-fold increase in virus discovery rate over the targeted methods, and 72.7-fold over symptom-based methods. The average number of viruses reported per publication has also increased proportionally over time. The use of HTS has driven the described national virome recently by 549 new-to-science viruses; all are indigenous. This report represents the first catalogue of viruses associated with indigenous species of a country. We provide evidence that the application of HTS to samples of Aotearoa New Zealand’s unique fauna and flora has driven indigenous virus discovery, a key step in the process to understand the role of viruses in the biological diversity and ecology of the land, sea, and air environments of a country.